Concrete Delamination Analysis and Repair Methods in Residential Buildings - Reynold Andika Pratama; Yuli Sulistyohadi; Jody Sutiawan; Pangeran Holong Sitorus (International Journal Multidisciplinary Science, 2025)
Laminated concrete involves removing a thin layer from the concrete surface, making it prone to abrasion and weakening the structure. This delamination, often termed concrete weathering, produces a "drumming" sound when the surface is hammered, signaling the need for repair to prevent further spread. Delamination can result from poor concrete mix or casting issues, such as segregation when fresh concrete is poured. Quality control is crucial before pouring concrete into formwork for columns and walls. Checks like the slump test ensure proper workability, while concrete test specimens verify the mix meets the 28-day characteristic compressive strength. Casting concrete from heights exceeding 1.5 meters can cause delamination by segregating fine and coarse aggregates. Repairs for delaminated surfaces include grouting, plastering, or injecting. In a 4-story house construction project, plastering is often preferred due to the ready availability of materials like fine sand and cement, making it an effective solution. To summarize, delamination weakens concrete structures and requires timely detection and repair. Proper quality control during concrete mixing and casting, including slump tests and strength verification, helps prevent segregation and delamination. For repairs, plastering is a practical choice in multi-story projects due to material accessibility